2020
DOI: 10.1016/j.dcmed.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Pharmacological Strategies to Explore the Regulatory Mechanism of Ma Xing Shi Gan Decoction on COVID-19

Abstract: Objective To use systematic pharmacological strategies to explore the regulatory mechanisms of Ma Xing Shi Gan Decoction (MXSGD) against the coronavirus disease 2019 (COVID-19). Methods Data on the compounds and targets of MXSGD were collected from the Traditional Chinese Medicene Systems Parmacology Database and Analysis Platform (TCMSP) and TCM Databases@Taiwan. Data on ACE2-related targets and the protein-protein interaction (PPI) were collected from the String datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The active compounds of another herbal formula may act on ACE2, IL-6, and GM-CSF. Gancainin H and liquorice glycide E (from liquorice) act on ACE2, and glycyrin targets IL-6 and GM-CSF, orchestrating multiple signaling pathways to attenuate inflammation and viral infection, thus preventing lung and heart injury caused by SARS-CoV-2 (Shi-Ying et al, 2020).…”
Section: Protecting Target Organsmentioning
confidence: 99%
“…The active compounds of another herbal formula may act on ACE2, IL-6, and GM-CSF. Gancainin H and liquorice glycide E (from liquorice) act on ACE2, and glycyrin targets IL-6 and GM-CSF, orchestrating multiple signaling pathways to attenuate inflammation and viral infection, thus preventing lung and heart injury caused by SARS-CoV-2 (Shi-Ying et al, 2020).…”
Section: Protecting Target Organsmentioning
confidence: 99%
“…From the KEGG enrichment analysis, our results indicated that the key signaling pathways of AE against COVID-19 are TNF, TLR, HIF-1 and NLRs, which are closely related to in ammation, immunity and oxidation process. Similarly, many studies also reported that the anti-COVID-19 mechanisms of TCM prescriptions with AE might be related to these above pathways 38,39,40 . In particular, TNF pathway has been reported to be involved in a variety of physiological and pathological processes, such as cell proliferation, apoptosis, and modulation of immune responses and induction of in ammation 41,42 , so it may play an important role in the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…From the KEGG enrichment analysis, our results indicated that the key signaling pathways of AE against COVID-19 are TNF, TLR, HIF-1 and NLRs, which are closely related to inflammation, immunity and oxidation process. Similarly, many studies also reported that the anti-COVID-19 mechanisms of TCM prescriptions with AE might be related to these above pathways [ 38 40 ]. In particular, TNF pathway has been reported to be involved in a variety of physiological and pathological processes, such as cell proliferation, apoptosis, and modulation of immune responses and induction of inflammation [ 41 , 42 ], so it may play an important role in the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%